2015
DOI: 10.1016/j.bbi.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Response and habituation of pro- and anti-inflammatory gene expression to repeated acute stress

Abstract: Introduction Acute stress induces increases in plasma inflammatory mediators, which do not habituate to repeated stress. Inflammation is a risk factor for age-related illnesses, highlighting the need to understand factors controlling inflammation. No studies have examined changes in pro- and anti-inflammatory gene expression in response to repeated acute stress in humans. Methods RNA was isolated from peripheral blood before, 30 and 120 minutes after exposure of n=32 healthy human participants to the Trier S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 49 publications
(73 reference statements)
3
24
0
5
Order By: Relevance
“…Additionally results from this study demonstrates that chronic sleep loss does not produce the typical pattern of habituation with repeat exposure with respect to HPA (Grissom et al, 2009) and IL-6 responses (the latter when measured on a cellular level (McInnis et al, 2015)). While it is adaptive for the HPA axis to habituate to non-harmful stressors, sleep is a necessary biological resource (Everson et al, 2009; Hamilton et al, 2007; McEwen, 2006), so habituation to chronic sleep loss may be harmful rather than adaptive.…”
Section: Discussionmentioning
confidence: 66%
“…Additionally results from this study demonstrates that chronic sleep loss does not produce the typical pattern of habituation with repeat exposure with respect to HPA (Grissom et al, 2009) and IL-6 responses (the latter when measured on a cellular level (McInnis et al, 2015)). While it is adaptive for the HPA axis to habituate to non-harmful stressors, sleep is a necessary biological resource (Everson et al, 2009; Hamilton et al, 2007; McEwen, 2006), so habituation to chronic sleep loss may be harmful rather than adaptive.…”
Section: Discussionmentioning
confidence: 66%
“…Individuals vary markedly in the magnitude of change in inflammatory mediators in response to acute stress and there is some evidence that this variability is relatively stable across time (Von Kanel 2006; Breines et al, 2014; Lockwood, John-Henderson, Marsland, 2016), and may even increase in magnitude in response to repeat testing (Rohleder, 2014; McInnis et al, 2015). Thus, it is conceivable that there is a meaningful distribution of differences in stress reactivity that may form a physiological basis for differences in susceptibility to disease.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty min after stress, as many as two-thirds of the study participants exhibited cortisol levels that were lower than pre-test levels. According to previous studies, a peak response in cortisol is expected to occur 15-25 min after a laboratory mental stressor followed by a rapid decline reaching below pre-test levels (Kunz-Ebrecht et al 2003, Brydon 2010, McInnis et al 2015. However, in one study of healthy volunteers, cortisol levels were shown to be lower already 20 min after stress compared with pre-test levels (Steptoe et al 2001).…”
Section: Negative Correlations Between Stress-induced Changes In Neutmentioning
confidence: 96%